Tertiary education for the knowledge society. Volume 1, Special features : governance, funding, quality - Santiago, Paulo; Organizace pro ekonomickou spolupráci a rozvoj (Paris : Organisation for Economic Co-operation and Development, 2008)
This book provides a thorough international investigation of tertiary education policy across its many facets – governance, funding, quality assurance, equity, research and innovation, academic career, links to the labour market and internationalisation. It presents an analysis of the trends and developments in tertiary education; a synthesis of research-based evidence on the impact of tertiary-education policies; innovative and successful policies and practices that countries have implemented; and tertiary-education policy options. The report draws on the results of a major OECD review of tertiary education policy – the OECD Thematic Review of Tertiary Education -- conducted over the 2004-08 period in collaboration with 24 countries around the world.
Pod názvem: OECD
Obsahuje bibliografii
Keywords: vzdělávání; vysoké školy; vzdělávání dospělých; profesní příprava; znalostní společnost; vyšší vzdělání; studie; education; universities and colleges; adult learning; professional training; knowledge society; studies